ICU admissions for sepsis: clinical profiles and outcomes in a tertiary care setting, SSG hospital, Vadodara: single-center, descriptive observational study - Bhudhrani, Divyang; Narasimhan, Vasuprada; Patel, Nachiket M.; Mehta, Divya A.; Kumar, Amit (International Journal of Research in Medical Sciences, 2024)
Background: Sepsis is a critical condition leading to high morbidity and mortality rates, especially in intensive care units (ICUs). This study aimed to evaluate the outcomes of patients admitted with sepsis in ICUs across western India, focusing on mortality rates, length of ICU stay, and factors influencing patient outcomes. Methods: A single-center, descriptive observational study was conducted using medical records from January 2023 to December 2023. The study included 100 patients diagnosed with sepsis upon ICU admission in, SSG hospital Vadodara. Data were collected on demographic characteristics, comorbidities, severity of sepsis (using sofa scores), treatment interventions, ICU length of stay, and mortality outcomes. Statistical analyses were performed to identify predictors of mortality and prolonged ICU stay. Results: The overall ICU mortality rate among sepsis patients was 32.5%. The median ICU length of stay was 10 days, with a range of 2 to 45 days. Mortality rates were significantly higher in patients with comorbidities such as diabetes (40.2%) and chronic kidney disease (37.8%). The sofa score at admission was a strong predictor of both mortality and prolonged ICU stay. Among the survivors, 65% required mechanical ventilation, and 45% developed acute kidney injury. Early initiation of appropriate antibiotic therapy and source control were associated with improved outcomes. Conclusions: Sepsis in ICU patients in western India is associated with high mortality and significant resource utilization. Early diagnosis and timely management, particularly in patients with high sofa scores and comorbid conditions, are crucial for improving patient outcomes.